2005
DOI: 10.1210/jc.2005-1498
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Ob-Rb Receptor Isoform in the Human Digestive Tract during Fetal Development

Abstract: The strong expression of leptin, in amniotic fluid when fetuses begin swallowing then in the gastric mucosa, and the early presence of Ob-Rb in mucosae suggest a possible role for leptin, exerted endoluminally and in a paracrine pathway, in the developmental process (growth and/or maturation) of the human digestive tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…19,20 Beside its important role in the normal physiology of the gastrointestinal tract, the trophic effects of leptin on the small intestinal mucosa have been demonstrated in certain gastrointestinal disorders. 21,22 In recent studies, we have demonstrated the positive effect of leptin on intestinal recovery following intestinal ischemia-reperfusion 11 and on gut re-growth following massive small bowel resection in a rat model.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 Beside its important role in the normal physiology of the gastrointestinal tract, the trophic effects of leptin on the small intestinal mucosa have been demonstrated in certain gastrointestinal disorders. 21,22 In recent studies, we have demonstrated the positive effect of leptin on intestinal recovery following intestinal ischemia-reperfusion 11 and on gut re-growth following massive small bowel resection in a rat model.…”
Section: Methodsmentioning
confidence: 99%
“…During fetal development, locally produced leptin appears to regulate the growth and/or maturation of the digestive tract (Aparicio et al 2005a). Postnatally, leptin modulates local immune responses, and has been shown to exert either pro-or anti-inflammatory activities in the intestine, depending on the experimental model (Siegmund et al 2002, Bozkurt et al 2003, Cakir et al 2004, Sitaraman et al 2004, Adeyemi et al 2005, Karagiannides & Pothoulakis 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of leptin immunopositivity in the oesophageal epithelium of bony fish has not yet been reported, but we suggested that leptin could be involved in the oesophageal functions and particularly in mucous secretion. We also hypothesised that leptin distribution is more extensive during development than in adults as reported in human foetuses (Aparicio et al 2005).…”
Section: Discussionmentioning
confidence: 88%